Efficacy of heads‐up CPR compared to supine CPR positions: Systematic review and meta‐analysis. Issue 3 (24th May 2022) - Varney, Joseph; Motawea, Karam R.; Mostafa, Mostafa R.; AbdelQadir, Yossef H.; Aboelenein, Merna; Kandil, Omneya A.; Ibrahim, Nancy; Hashim, Hashim T.; Murry, Kimberly; Jackson, Garrett; Shah, Jaffer; Boury, Maty; et al.
Abstract: Background and Aim: Cardiopulmonary resuscitation (CPR) in full‐coded patients requires effective chest compressions with minimal interruptions to maintain adequate perfusion to the brain and other vital organs. Many novel approaches have been proposed to attain better organ perfusion compared to traditional CPR techniques. The purpose of this review is to investigate the safety and efficacy of heads‐up CPR versus supine CPR. Methods: We searched PubMed Central, SCOPUS, Web of Science, and Cochrane databases from 1990 to February 2021. After the full‐text screening of 40 eligible studies, only seven studies were eligible for our meta‐analysis. We used the RevMan software (5.4) to perform the meta‐analysis. Results: In survival outcome, the pooled analysis between heads‐up and supine CPR was (risk ratio = 0.98, 95% confidence interval [CI] = 0.17–5.68, p  = 0.98). The pooled analyses between heads‐up CPR and supine CPR in cerebral flow, cerebral perfusion pressure and coronary perfusion pressure outcomes, were (mean difference [MD] = 0.10, 95% CI = 0.03–0.17, p  = 0.003), (MD = 12.28, 95% CI = 5.92–18.64], p  = 0.0002), and (MD = 8.43, 95% CI = 2.71–14.14, p  = 0.004), respectively. After doing a subgroup analysis, cerebral perfusion was found to increase during heads‐up CPR compared with supine CPR at 6 min CPR duration and 18 to 20 min CPR duration as well. Conclusion: Our study suggests that heads‐up CPR is associated with better cerebral and coronary perfusion compared to the conventional supine technique in pigs' models. However, more research is warranted to investigate the safety and efficacy of the heads‐up technique on human beings and to determine the best angle for optimization of the technique results.